Regulation of the glucocorticoid response to stress-related disorders by the Hsp90-binding immunophilin FKBP51 - Galigniana, Natalia Maricel (2012)
Immunophilin is the collective name given to a family of proteins that bind immunosuppressive drugs: Some immunophilins are Hsp90-binding cochaperones that affect steroid receptor function. Mood and anxiety disorders are stress-related diseases characterized by an impaired function of the mineralocorticoid and glucocorticoid receptors, two of the major regulatory elements of the hypothalamus-pituitary-adrenocortical axis. Genetic variations of the FK506-binding protein of 51-kDa, FKBP51, one of the immunophilins bound to those steroid receptor complexes, were associated with the effectiveness of treatments against depression and with a major risk-factor for the development of post-traumatic stress disorders. Interestingly, immunophilins show polymorphisms and some polymorphic isoforms of FKBP51 correlate with a greater impairment of steroid receptor functions. In this review, we discuss different aspects of the role of FKBP51 in such steroid receptor function and the impact of genetic variants of the immunophilin on the dysregulation of the stress response.